Leading the way – presence of brown bear Ursus arctos, lynx Lynx lynx and grey wolf Canis lupus underlines the integrity and corridor function of the upper Neretva Valley in Bosnia and Herzegovina - Manuela Habe (Natura Sloveniae)
Despite its connecting character to the Sutjeska National Park in the North-East, the course of the upper Neretva (Ulog and Borač valley) in Bosnia and Herzegovina (BiH), has to date not been an area of focus for carnivore research. With the aim of contributing to an improved understanding of the present distribution of large and endangered carnivores in this area, a field survey was conducted during the Neretva Science Week 2022. Opportunistic data collection was carried out along a predefined road transect (20 km) and six line transects (13 km) tracked by foot. Additionally, reports of mammal signs for six corresponding research sites along the Neretva were registered. Altogether, at least 15 mammal species could be distinguished. From the identified carnivores, four are listed in Annex II of the Habitats Directive. Furthermore, the signs of lynx presence, in addition to brown bear and grey wolf, highlight the connectivity value of the upper Neretva in its current state. Based on information from local practitioners, the main threats to large carnivores are hunting pressure and a negative perception as competitors. A likely decline in habitat quality and fragmentation, due to the planned hydropower plants expansion and logging activities, exacerbate these threats. Consequently, further systematic monitoring is recommended to assess the possible impact of human driven environmental changes.